THE ROLE OF COMMUNICATION MANAGEMENT IN SPORTS WITH SPECIAL EMPHASIS ON HANDBALL - Denkova, Jadranka; Bajramovska, Mirjeta (Journal of process management and new technologies, 2018)
Communication management plays a significant role in all aspects of social life and is increasingly representing an inevitable segment for the successful functioning of organizations. Hence, the topic of this research in order to perceive how is communication management perceived in the world of sport in the Republic of Macedonia. The main emphasis is on researching the leadership for communication in handball in the Republic of Macedonia. The significance of this work is especially pointed out in terms of the fact that sport is the basis for the development of young people in a country, both physically and mentally, and should be an indication of the creation of healthy individuals. Therefore, the internal and external communication in sports clubs will affect their achievements, the development of their image and the achievement of efficiency of sports organizations. Sport is a sensitive topic from the aspect of being directly related to the citizens as users of their services. Whether these clubs will be successful will depend on how they function, what is their approach, the quality, how they communicate with the public, how they communicate inside the clubs and how they communicate on a wider level, sports clubs among themselves. Bearing in mind that this work is concentrated on a serious methodological approach which analyses relevant documents, statistical indicators, as well as qualitative analysis of an interview, it can be concluded that very little attention is paid to communication management, its significance and role is not properly understood and all this is further reflected in the negative results in sports in the Republic of Macedonia. In addition, there is a need for legal changes, training of the involved people in the field that will enable more serious approach to this scientific discipline, which would improve the efficiency of sports organizations in the Republic of Macedonia.